The Influence Of Compensation, Workload And Working Environment On Employee Work Productivity At PT Hanchen Industrial Indonesia - Heru Hermawan; Rauly Sijabat; M. Fadjar Darmaputra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study began with findings that occurred at PT Hanchen Industrial Indonesia, where employees were less than optimal in carrying out their work. It can be seen from the decline in employee work productivity so that the company's targets are not achieved. In this research, it was found that there were several factors that influenced employee work productivity, including compensation, workload and work environment. The aim of this research is to identify and analyze the influence of compensation, workload and work environment on employee work productivity at PT Hanchen Industrial Indonesia. The sample in this study used the Slovin formula with a total of 75 respondents. Data analysis in this research was carried out using the multiple regression method with the help of SPSS version 23 software. The results of the research show that the compensation variable has a positive and significant effect on employee work productivity as evidenced by the t-count value of 4,454 > t-table 1,993, workload has a positive and significant effect on employee work productivity as evidenced by the t-count value of 2,621 > t-table 1.993 and the work environment has no effect and is not significant on employee work productivity as evidenced by the t-count value (-1.313) < t-table 1.993. Simultaneously, compensation, workload and work environment have a significant positive effect on employee work productivity as proven by the calculated F-value of 11,317 > the F-table value of 2.73. The Adjusted R Square determination value is 0.295 or 29.5%.